Defense strategies of a myrmecophyte: survival implications for Duroia hirsuta in mutualism with Myrmelachista schumanni and Azteca spp. in the Yasuní Amazonian Forest - Rodríguez Ortega, Camila Viviana (2023)
Duroia hirsuta K. Schum. (Rubiaceae) is a myrmecophyte that associates with ant colonies from some species such as Myrmelachista schumanni or Azteca spp and three other Neotropical Genera. It is known that M. schumanni protects its host plants against herbivory and eliminates adjacent allospecific plants in the surroundings of its host tree, while Azteca seems to just provide indirect protection from herbivores. This study aims to determine whether physico-chemical defenses, ‘leaf dry matter content, herbivory,’ and secondary growth of D. hirsuta are influenced by the identity of the associated ants (after 12 years of uninterrupted mutualism) within an Amazonian 50 ha ‘forest dynamic plot’. For this we studied D. hirsuta trees with (i) M. schumanni and (ii) Azteca spp as indirect defenses treatments for comparison. We hypothesize that the individuals of D. hirsuta in mutualism with M. schumanni exhibit a lower inversion in physical and chemical defenses due to the advantages this ant species provides showing a lower damage by herbivory, and a higher secondary growth rate in contrast to the individuals associated with Azteca m.spp. For the growth record we used a digital caliper to obtain the DBH of the trees in the year 2019 to compare it withthe measurements of previous years (i.e. 2007, 2013 and 2017). We collected mature leaves to evaluate the percentage of herbivory, shearing resistance and LDMC. The percentage of herbivory was calculated with a digital tool in situ. To measure shearing resistance, we used a handmade steel instrument of standardized movements within a dual-range digital force sensor screwed with a peg- like folded steel sheet that supported a razor blade. In the chemical analyses we used young leaves and performed an ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). We found secondary growth rate and shearing resistance significant differences between our treatments with higher values for the trees in mutualism with M. schumanni. We also found no correlation between herbivory, secondary growth, LDMC, and shearing resistance, suggesting no evidence of trade-offs between these variables. Our results, based on our long-term data of ants’ presence/absence and given that absence of ants involves the death of the tree suggest that Duroia’s trees present an obligate mutualism with ants for survival in the tropical forests.